Transforming Nigeria's Education: Insights from Indonesia's Policy Reinforcement - Adeoye, Moses Adeleke; Nurjanah, Ratih Laily; Widiana, I Wayan; Prastikawati, Entika Fani (Mimbar Ilmu, 2024)
The Nigerian education system continues to face numerous challenges, including limited access, poor educational quality, and inequalities in learning outcomes. These challenges necessitate effective policy reforms to enhance educational quality and achieve sustainable development goals. This study aims to examine the potential transformation of Nigeria's education system by drawing lessons from the success of educational policy reforms in Indonesia. The study employs a comparative analysis method by examining key elements of Indonesia's educational policies, their implementation strategies, and their impacts on educational outcomes. The analysis explores contextual similarities and differences between the two countries to identify best practices and transferable lessons for Nigeria. Data were gathered from various sources, including policy reports, academic studies, and official publications, and were qualitatively analyzed to provide in-depth insights. The findings reveal that Indonesia's educational policies, such as compulsory education programs, teacher quality improvement initiatives, and the strengthening of vocational education, have positively impacted both access to and quality of education. These practices can be adapted to Nigeria’s context to address similar challenges. However, the implementation of such policies in Nigeria requires adjustments to suit the country’s unique social, economic, and cultural conditions. In conclusion, this study emphasizes that well-directed and sustainable policy reforms can bring transformative changes to a country's education system.